A Historiographical Approach to the Qur’an and Shari’a in Late 19th Century India: the Case of Chiragh ‘Ali - Mohomed, Carimo (História da Historiografia: International Journal of Theory and History of Historiography, 2015)
Analysing the book The Proposed Political, Legal, and Social Reforms in the Ottoman Empire and Other Mohammadan States (1883) and undertaking a historical contextualization, this paper problematizes the epistemis and epistemological framework underlying the articulation of Chiragh ‘Ali’s discourse, focusing on how he viewed the Qur’an and Shari’a according to the intellectual debates in the 19th century. Often refuting, in his writings, missionary and Orientalist criticisms of Islam as being hostile to reason and incapable of reform, Chiragh ‘Ali rather argued that the Islamic legal system and schools were human institutions capable of modification. While defending that the Qur’an taught religious doctrine and rules for morality, Chiragh ‘Ali held the opinion that it did not support a detailed code of immutable civil law or dictate a specific political system, drawing on an examination of the traditional sources of the Islamic law and methods to overcome the rigidity of traditional theologians.